PENGARUH PERBEDAAN KETINGGIAN TEMPAT TERHADAP KANDUNGAN METABOLIT SEKUNDER PADA GULMA BABADOTAN (Ageratum conyzoides L.) - Rino H.H. Katuuk; Sesilia A. Wanget; Pemmy Tumewu (COCOS, 2018)
Abstract This study aims to look for the effect of site height on the phytochemical content of weed babadotan Ageratum Conyzoides L. This research was carried out at the Samratulangi University Integrated Laboratory in Manado, on September to October 2018. The study used extraction metode and the results of the study were presented in table form. The results showed that there was a difference in the content of secondary metabolites in babadotan (Ageratum Conyzoides L.) in different of height. The secondary metabolite namely saponin found in the middle plain (700 m asl) but not found in the lowlands (320 m asl) using extraction tests with ethanol solvents. Key words :Â  secondary metabolite; site height; saponin